Scoping Review Intervensi Perawat Pada Manajemen Stemi Intra Rumah Sakit - Faisol Faisol; Erna Rochmawati (Universitas Pahlawan Tuanku Tambusai, 2026)
ST-Elevation Myocardial Infarction (STEMI) is a cardiovascular emergency that is highly time-dependent; delays in reperfusion are closely associated with increased complications and mortality. In this context, nurses play a strategic role as timekeepers throughout the STEMI care continuum. This narrative review aimed to summarize recent evidence regarding nursing interventions in STEMI management. The method used was a narrative review with literature searches conducted in PubMed, Scopus, and ScienceDirect databases for the period 2020–2025 using the keywords “Nursing Intervention” and “Management STEMI.” Included articles were original research studies with free full-text/open-access availability. Of the 1,663 articles identified, 189 articles were reviewed in full text, and 8 articles met the inclusion criteria for analysis. The findings indicate that core nursing interventions include rapid chest pain triage and electrocardiogram acquisition, close hemodynamic monitoring, timely administration of antithrombotic therapy accompanied by contraindication screening and bleeding risk monitoring, activation of the STEMI code, interprofessional coordination and intra-hospital transfer, preparation of the catheterization laboratory, and structured handover. In conclusion, the standardization of nursing interventions with an emphasis on accelerating reperfusion has the potential to improve the quality and safety of STEMI care. Continuous time audits and prospective studies are needed to strengthen the evidence base for clinical implementation.